2012
DOI: 10.1016/j.bmc.2012.05.039
|View full text |Cite
|
Sign up to set email alerts
|

Highly potent macrocyclic BACE-1 inhibitors incorporating a hydroxyethylamine core: Design, synthesis and X-ray crystal structures of enzyme inhibitor complexes

Abstract: A series of P1-P3 linked macrocyclic BACE-1 inhibitors containing a hydroxyethylamine (HEA) isostere scaffold has been synthesized. All inhibitors comprise a toluene or Nphenylmethanesulfonamide P2 moiety. Excellent BACE-1 potencies, both in enzymatic and cell-based assays, were observed in this series of target compounds, with the best candidates displaying cell-based IC 50 values in the low nanomolar range. As an attempt to improve potency, a phenyl substituent aiming at the S3 subpocket was introduced in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 27 publications
0
25
0
Order By: Relevance
“…The alignment of these structures showed a reasonable conserved three-dimensional structure, except for two amino acids: (a) the conformation of ARG235 in the structure 3DV1 [30] clashes with the ligands from structures 2VIJ [26], 2VJ7 [31], 2VNM [32], 3K5C [16] and 4DPF [33], whereas other equivalent arginines, e.g. ARG296 in the structure 2VIJ [26], show no clashes; (b) the conformation of GLN73 in the structure 3DV1 [30], like most equivalent glutamines in this position, clashes with all ligands except those from the 3K5C [16], 3K5F [34] and 3IVH [35] structures.…”
Section: Preliminary Dockingmentioning
confidence: 99%
“…The alignment of these structures showed a reasonable conserved three-dimensional structure, except for two amino acids: (a) the conformation of ARG235 in the structure 3DV1 [30] clashes with the ligands from structures 2VIJ [26], 2VJ7 [31], 2VNM [32], 3K5C [16] and 4DPF [33], whereas other equivalent arginines, e.g. ARG296 in the structure 2VIJ [26], show no clashes; (b) the conformation of GLN73 in the structure 3DV1 [30], like most equivalent glutamines in this position, clashes with all ligands except those from the 3K5C [16], 3K5F [34] and 3IVH [35] structures.…”
Section: Preliminary Dockingmentioning
confidence: 99%
“…In the first example, Iqbal et al used this coupling as the cyclization step in the synthesis of constrained tri-or tetra-peptidomimetics with a biaryl linker (Scheme 11.13 illustrates a tripeptidomimetic (112)). 219 Fair to moderate yields were obtained for products containing 16-to 22-membered rings.…”
Section: Buchwald-hartwigmentioning
confidence: 98%
“…107 Inhibition of beta-secretase (BACE) also proved to be a very fertile arena for the discovery of a number of potent macrocyclic inhibitors (69)(70)(71). [108][109][110][111] Finally, macrocycles such as 72 have demonstrated that a several-fold potency improvement could be realized by the cyclization of linear renin inhibitors. 112 …”
Section: Non-hcv Protease Inhibitorsmentioning
confidence: 99%